Innovahubs: In-depth local actor and stakeholder analysis. Stakeholders’ assessment of the dynamic relationships and recommendations for sustainable scaling from within the Innovahubs - Diaz Espinosa, Anabell; Valencia, Eva; Woltering, Lennart; García Santiago, Jorge O.; Martínez, Oscar; Leal Gonzalez, Abel J.; Borrayo, Andrea; Loon, Jelle van (Bioversity International and the International Center for Tropical Agriculture, 2023)
The participation, engagement, and interaction of local actors in the Innovahubs is an essential part of the development and strengthening of the subnational innovation systems, so knowing and understanding the nature, identity and presence, and involvement of each type of actor over time is essential to understand their behavior and motivations to partake in the knowledge and innovation processes. Therefore, this report seeks to update on the actors participating in the relevant activities in the Innovahub, their activities, and the type of relations they have with other actors. This includes analyzing the level of involvement of each actor in the activities organized in the Innovahubs and mapping thestakeholder networks in Guatemala and Honduras. In addition, within the Innovahubs, one of the activities to be carried out is the scaling up of innovations (technologies or practices) that can better respond to the AgriLAC Initiative's impact areas of: a) Nutrition, Health and Food Security; b) Poverty Reduction, Livelihoods and Employment; c) Gender Equality, Youth and Social Inclusion; d) Climate Change Adaptation and Mitigation; e) Environmental Health and Biodiversity. As part of the work to be carried out this year, there was a need to evaluate the progress of the Innovahubs in these impact areas, and to know which innovations have the potential for scaling up from the regions. Because scaling up requires the support of different actors in each context, focus group sessions were conducted with scientists and local agents in the Innovahubs of Guatemala and Honduras to learn about their perception of the work done, and the potential innovations for scaling up in the following years. To this end, a system analysis was carried out to analyze to what extent the work of the Innovahubs in the first two years had responded to the needs of the region in the areas of impact, as well as to co-create potential proposals to solve the remaining challenges in a collaborative manner. The results showed that the areas where there has been the greatest impact are in Science, technology and infrastructure and in Society and culture. In comparison, the areas where there has been the least impact are Markets and Public policy and government.